(18)F-FDG-PET/MRI in the diagnostic work-up of limbic encephalitis - Deuschl, Cornelius (PLoS One, 2020)
INTRODUCTION: Limbic encephalitis (LE) is an immune-related, sometimes paraneoplastic process of the central nervous system. Initial diagnosis and treatment are based on the clinical presentation as well as antibody profiles and MRI. This study investigated the diagnostic value of integrated (18)F-FDG-PET/MRI in the diagnostic work-up of patients with LE for a cerebral and whole-body imaging concept. MATERIAL AND METHODS: Twenty patients with suspected LE were enrolled in this prospective study. All patients underwent a dedicated PET/MRI protocol of the brain as well as the whole-body. Two neuroradiologists, one body radiologist and one nuclear medicine physician performed blinded consensus readings of each corresponding MRI and PET/MRI dataset of the brain and whole-body. Diagnostic confidence was evaluated on a Likert scale. RESULTS: Based on integrated PET/MRI 19 / 20 patients were found to show morphologic and / or metabolic changes indicative of LE, whereas sole MRI enabled correct identification in 16 / 20 patients. Three patients with negative MRI showed metabolic changes of the limbic system or extra-limbic regions, shifting the diagnosis from (negative) MRI to positive for LE in PET/MRI. Whole-body staging revealed suspected lesions in 2/20 patients, identified by MRI and PET, one confirmed as malignant and one false positive. Diagnostic confidence for cerebral and whole-body imaging reached higher scores for PET/MRI (cerebral: 2.7 and whole body: 4.8) compared to MRI alone (cerebral: 2.4 and whole body: 4.5). CONCLUSION: LE diagnosis remains challenging for imaging as it shows only subtle imaging findings in most patients. Nevertheless, based on the simultaneous and combined analysis of morphologic and metabolic data, integrated PET/MRI may enable a dual platform for improved diagnostic confidence and overall detection of LE as well as whole-body imaging for exclusion of paraneoplastic LE.